2018
DOI: 10.1371/journal.pone.0201743
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurses’ knowledge and practice on endotracheal suctioning of the intubated patient: A quantitative cross-sectional observational study

Abstract: IntroductionEndotracheal suction (ETS) is a common invasive procedure which is done to keep the airways patent by mechanically removing accumulated pulmonary secretions to all in patients with artificial airways. Many life-threatening complications can occur when the procedure is not performed correctly. Although the evidence-based recommendations regarding ETS are available, many of these have not been observed in nurse’s clinical practice. We assessed the intensive care nurses’ knowledge and practice of ETS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 28 publications
8
35
1
7
Order By: Relevance
“…The guideline contained 26 key recommendations in three procedural phases and 17 points of care (Hu et al, 2019). We also referred to questionnaires or checklists that have been used to assess ETS knowledge or practice of nurses in other countries such as the US and Australia (Leddy & Wilkinson, 2015;Mwakanyanga, Masika, & Tarimo, 2018;Negro et al, 2014;Rn et al, 2007). The questionnaire involved three domains: 1) demographic data, 2) nurses' awareness of, and 3) adherence to the ETS guideline.…”
Section: Questionnaire Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The guideline contained 26 key recommendations in three procedural phases and 17 points of care (Hu et al, 2019). We also referred to questionnaires or checklists that have been used to assess ETS knowledge or practice of nurses in other countries such as the US and Australia (Leddy & Wilkinson, 2015;Mwakanyanga, Masika, & Tarimo, 2018;Negro et al, 2014;Rn et al, 2007). The questionnaire involved three domains: 1) demographic data, 2) nurses' awareness of, and 3) adherence to the ETS guideline.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…It revealed that considerable gaps exist between the evidence-based ETS practices and the current clinical practices (Graham & Logan, 2004). In order to bridge the evidence-practice gap, theoretical education or training alone may not be adequate to in uence practice change (Ansari et al, 2012;Heidari & Shahbazi, 2017;Mwakanyanga et al, 2018). Routine training together with individual or group support like post-training follow-up, coaching, using of support documents like unit or hospital-level ETS regulations, web or mobile applications, checklists, reminders, userfriendly pictures, and pocket versions of the guideline could potentially elevate the knowledge level and practical ETS skills of intensive care nurses (McKillop, 2004;Mwakanyanga et al, 2018;Straus, Tetroe, & Graham, 2013).…”
Section: Adherence To Ets Recommendations During Practicementioning
confidence: 99%
“…Strategies in the form of educational programmes should be implemented to enhance the nurses’ knowledge. This is especially important as previous studies conducted on nurses’ knowledge regarding ETT cuff pressure revealed differences in ICU nurses’ knowledge, leading to varying practices (Abubaker et al 2019 ; Jordan 2011 ; Jordan, Van Rooyen & Venter 2012 ; Mohammed et al 2016 ; Mwakanyanga, Masika & Tarimo 2018 ). A study by Mohammed et al ( 2016 ) showed that an educational programme including discussion groups and formal lectures accompanied by suitable teaching aids, such as handouts, posters, coloured pictures and a programme booklet, improved the knowledge of the nurses regarding ETT cuff pressure.…”
Section: Introductionmentioning
confidence: 99%
“…hemodinamika merupakan suatu pengkajian fisiologis yang penting dalam perawatan pasien -pasien kritis. Hasil penelitian menyebutkan mayoritas perawat ICU (69,9%) tahu indikasi prosedur, (77,7%) tahu tindakan yang harus diambil jika terjadi perubahan mendadak pada monitor EKG 14 .…”
Section: Monitoringunclassified